PENGARUH STRES KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PEGAWAI NON MEDIS) RSU. ROYAL PRIMA MEDAN - KHOMEINY YUNIOR; LAMTIO SIANTURI (LP2MTBM MAKARIOZ, 2022)
The purpose of this research is to examine and analyze the effect of work stress, work motivation and work environment on employee performance. To test the effect of work stress, work motivation and work environment on employee performance, a case study of non-medical staff at RSU. Royal Prima Medan. The decline in employee performance is influenced by work stress, work motivation and work environment which causes a decrease in employee performance in non-medical employees of RSU. Royal Prima Medan. The population in this study was 137 people and the sample in this study was 102 people. The research method uses multiple linear regression analysis techniques. The results of the calculation of hypothesis testing partially obtained tcount < ttable or -.540 < 1.984 and significantly obtained 0.591 > 0.05, partially obtained tcount > ttable or 2.364 > 1.984 and significantly obtained 0.020 <0.05, partially obtained tcount > ttable or 4.238 > 1.984 and significantly obtained 0.000 <0.05, The results of the coefficient of determination test obtained an Adjusted R Square value of 0.255 this means 25.5% of the variation in the dependent variable which can be explained by variations in the independent variables while the remaining 74.5% (100% - 25.5%) is explained by other variables not examined in this study. The conclusions in this study indicate that simultaneously work stress, work motivation and work environment on employee performance (a case study of non-medical employees at Royal Prima Medan Public Hospital) and partially work stress, work motivation and work environment on employee performance (case study of non-medical employees RSU Royal Prima Medan)Keywords: Stress, Motivation, Work Environment, Employee Performanc